Failure to detect an association between aggressive periodontitis and the prevalence of herpesviruses. (19th November 2012) - Stein, Jamal M.; Said Yekta, Sareh; Kleines, Michael; Ok, Dilara; Kasaj, Adrian; Reichert, Stefan; Schulz, Susanne; Scheithauer, Simone
Abstract Background Herpes simplex virus type 1 (HSV‐1), human cytomegalovirus (HCMV) and Epstein–Barr virus (EBV) have been suspected to play a causal role in periodontitis pathogenesis. The aim of this study was to determine the prevalence of these viruses in subgingival plaque samples of Caucasian patients with generalized aggressive periodontitis compared to periodontally healthy controls. Methods A total of 65 patients with aggressive periodontitis and 65 unmatched controls from Germany were investigated in the study. Subgingival plaque samples were analysed for the presence of HSV‐1, EBV and HCMV by quantitative real‐time polymerase chain reaction assays. Viral antibody titres were determined quantitatively by immunosorbent assays. Results DNA of HSV‐1 and HCMV were detected in 1.5% of the patients and controls, whereas EBV DNA was present in 10.8% and 13.9% respectively. Detection rates of serum IgG against HSV‐1 (76.1% versus 73.9%), EBV (98.5% versus 96.9%), HCMV (47.7% versus 46.2%) and IgM levels against HSV‐1 (6.2% versus 1.5%), EBV (0% versus 0%), HCMV (0% versus 1.5%) did not significantly differ between patients and controls. Conclusion The data of our study do not suggest any contribution of HSV‐1, EBV or HCMV to aggressive periodontitis in a German population. Ethnic and methodological aspects might have caused conflicting results of previous studies.